The molecular and cellular action properties of artemisinins: what has yeast told us? - Chen Sun; Bing Zhou (Microbial Cell, 2016)
Artemisinin (ART) or Qinghaosu is a natural compound possessing superior anti-malarial activity. Although intensive studies have been done in the medicinal chemistry field to understand the structure-effect relationship, the biological actions of artemisinin are poorly understood and controversial. Due to the current lack of a genetic amiable model to address this question, and an accidental finding made more than a decade ago during our initial exploratory efforts that yeast Saccharomyces cerevisiae can be inhibited by artemisinin, we have since been using the baker’s yeast as a model to probe the molecular and cellular properties of artemisinin and its derivatives (ARTs) in living cells. ARTs were found to possess potent and specific anti-mitochondrial properties and, to a lesser extent, the ability to generate a relatively general oxidative damage. The anti-mitochondrial effects of artemisinin were later confirmed with purified mitochondria from malaria parasites. Inside some cells heme appears to be a primary reducing agent and reduction of ARTs by heme can induce a relatively nonspecific cellular damage. The molecular basis of the anti-mitochondrial properties of ARTs remains not well elucidated yet. We propose that the anti-mitochondrial and heme-mediated ROS-generating properties constitute two cellcidal actions of ARTs. This review summarizes what we have learned from yeast about the basic biological properties of ARTs, as well as some key unanswered questions. We believe yeast could serve as a window through which to peek at some of the biological action secrets of ARTs that might be difficult for us to learn otherwise.